2020
DOI: 10.1088/1742-6596/1442/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of biodegradable plastics using corn starch and corn husk as the fillers as well as chitosan and sorbitol

Abstract: Bio plastics are polymers prepared from renewable materials. In this study, maize-derived cornstarch and milled corn husk were used as the base material and filler, respectively. Corn husk powder with two-grain sizes of 150 mesh and 200 mesh, respectively, were used. Chitosan was used at concentrations of 0.02 %, 0.04 %, 0.06 %, 0.08 %, and 0.1 % by weight at a constant ratio of 1:1 to cornhusk powder and maize for improving the mechanical properties of bio plastics. The mixture was diluted using a solution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results show good performance of the product obtained. In general, however, much bioplastic research is focused on the use of starchy-rich and renewable plant materials such as maize [24], potatoes [25], wheat [26], manioc, and vegetable oils [27,28]. However, the production of bioplastics from food precursors, in addition to the fact that it can often be costly, poses a further problem: obtaining bioplastics from food crops means taking away land and water from food production, which should be used for human consumption.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The results show good performance of the product obtained. In general, however, much bioplastic research is focused on the use of starchy-rich and renewable plant materials such as maize [24], potatoes [25], wheat [26], manioc, and vegetable oils [27,28]. However, the production of bioplastics from food precursors, in addition to the fact that it can often be costly, poses a further problem: obtaining bioplastics from food crops means taking away land and water from food production, which should be used for human consumption.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Ghanbarzadeh et al found that the films made based on pure starch are brittle and fragile, especially compared to films made from cornstarch, which has a lower concentration of amylose content [16]. D. Amalia et al In (2020) He used cornstarch derived from corn and ground corn husk as base material and filler, respectively to improve the mechanical properties of bioplastic [17]. M. K. Maricela et al In (2019) studied BOP based on rice starch and cornstarch packaging applications, various bioplastic films are synthesized with diverse formulations such as starch, gelatin, citric acid, and glycerin.…”
Section: Introductionmentioning
confidence: 99%
“…It can strengthen biopolymers, improve mechanical properties and reduce the high-water sensitivity of bioplastic layers [5]. Chitosan is usually used as a preservative and can increase the number of hydrogen bonds in the polymer chain, where these bonds contribute to the overall strength of the bioplastic [6]. Meanwhile, kaolin also plays a role in improving the mechanical properties of bioplastics based on increasing the barrier properties of CO2, O2, and moisture [7].…”
Section: Introductionmentioning
confidence: 99%